Renin-angiotensin system inhibitors improve the clinical outcomes of COVID-19 patients with hypertension - Juan Meng; Guohui Xiao; Juanjuan Zhang; Xing He; Min Ou; Jing Bi; Rongqing Yang; Wencheng Di; Zhaoqin Wang; Zigang Li; Hong Gao; Lei Liu; et al. (Emerging Microbes and Infections)
The dysfunction of the renin-angiotensin system (RAS) has been observed in coronavirus infection disease (COVID-19) patients, but whether RAS inhibitors, such as angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II type 1 receptor blockers (ARBs), are associated with clinical outcomes remains unknown. COVID-19 patients with hypertension were enrolled to evaluate the effect of RAS inhibitors. We observed that patients receiving ACEI or ARB therapy had a lower rate of severe diseases and a trend toward a lower level of IL-6 in peripheral blood. In addition, ACEI or ARB therapy increased CD3 and CD8 T cell counts in peripheral blood and decreased the peak viral load compared to other antihypertensive drugs. This evidence supports the benefit of using ACEIs or ARBs to potentially contribute to the improvement of clinical outcomes of COVID-19 patients with hypertension.